Big elephants in small ponds: Do large traders make financial markets more aggressive? - Christina E. Bannier (Universität Kassel, Fachbereich Wirtschaftswissenschaften, 2004)
Market participants often suspect that large traders have a disproportionate effect on financial markets, increasing the aggressiveness of market responses. Prior studies have shown that the impact of a large trader on a currency crisis depends positively on his size and informational position. By contrast, this article highlights the role that market sentiment has on the impact of a large trader. If the market believes that fundamentals are weak, then the probability of a crisis depends positively on the trader's size but negatively on the precision of his information, with these effects reversed in a generally optimistic market. A large player, therefore, need not make market responses more aggressive.
Keywords: F31; D82; 330; currency crises; large traders; market sentiment; coordination; private and public information; Währungskrise; Devisenspekulation; Asymmetrische Information; Theorie